2018
DOI: 10.3126/jbs.v3i2.18919
|View full text |Cite
|
Sign up to set email alerts
|

Palmar dermatoglyphic traits in type 2 diabetes mellitus patients of Bengalee Hindu caste population of West Bengal, India: a cross-sectional study

Abstract: BackgroundDermatoglyphics is frequently used in understanding the proximity with non-communicable diseases including diabetes mellitus. Diabetes mellitus is one of the most common non-communicable diseases all over the world. The present study is an attempt to understand the association of palmer dermatoglyphic traits [i.e. a-b ridge count (ABRC), c-d ridge count (CDRC), presence of multiple number of axial triradii (t, t' & t") in a single palm, td ridge count (TDRC), atd angle, btd angle and ctd angle] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Apart from the efficacy of insulin and several oral hypoglycemic drugs used for the treatment of diabetes mellitus, they still have a number of side effects. Management of this metabolic disorder has a number of challenges for both patients and physicians 41. Investigations have revealed that traditional herbal medicines offer exciting opportunities, such as unlimited resources for the discovery of new drugs that can be used for the welfare of mankind.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the efficacy of insulin and several oral hypoglycemic drugs used for the treatment of diabetes mellitus, they still have a number of side effects. Management of this metabolic disorder has a number of challenges for both patients and physicians 41. Investigations have revealed that traditional herbal medicines offer exciting opportunities, such as unlimited resources for the discovery of new drugs that can be used for the welfare of mankind.…”
Section: Discussionmentioning
confidence: 99%